A broadly-applicable unified closure relation for Taylor bubble rise velocity in pipes with stagnant liquid. (March 2017) - Lizarraga-Garcia, E.; Buongiorno, J.; Al-Safran, E.; Lakehal, D.
Highlights: Taylor bubble velocity for inclined pipes with stagnant liquid for an ample range of properties and inclination angles that outperforms current correlations. The Taylor bubble velocity correlation is extracted from an ample numerical database generated with 3D CFD Direct Numerical Simulations with level set as the Interface Tracking Method. Taylor bubble velocity correlation for use in slug flow mechanistic models. CFD numerical method validated with vertical and inclined pipe experiments. Abstract: Taylor bubble velocity in slug flow is a closure relation which significantly affects the prediction of liquid holdup (or void fraction) and pressure gradient in mechanistic models of slug flow for oil and gas pipe applications. In this work, we use a validated Computational Fluid Dynamics (CFD) approach to simulate the motion of Taylor bubbles in pipes; the interface is tracked with a Level-Set method implemented in a commercial code. A large numerical database is generated covering the most ample range of fluid properties and pipe inclination angles explored to date ( Eo ∈ [10, 700], M o ∈ [ 1 × 10 − 6, 5 × 10 3 ], and θ ∈ [0°, 90°]). A unified Taylor bubble rise velocity correlation is extracted from that database. The new correlation predicts the numerical database with 8.6% absolute average relative error and a coefficient of determination R 2 = 0.97, and other available experimental data with 13.0% absolute average relative error and R 2 = 0.84 outperforming existing correlations and models.